Regulatory mechanism of Reelin activity: a platform for exploiting Reelin as a therapeutic agent - Hattori, Mitsuharu (Frontiers in Molecular Neuroscience, 2025)
Reelin is a secreted glycoprotein that was initially investigated in the field of neuronal development. However, in recent decades, its role in the adult brain has become increasingly important, and it is now clear that diminished Reelin function is involved in the pathogenesis and progression of neuropsychiatric and neurodegenerative disorders, including schizophrenia and Alzheimer’s disease (AD). Reelin activity is regulated at multiple steps, including synthesis, posttranslational modification, secretion, oligomerization, proteolytic processing, and interactions with extracellular molecules. Moreover, the differential use of two canonical receptors and the presence of non-canonical receptors and co-receptors add to the functional diversity of Reelin. In this review, I summarize recent findings on the molecular mechanisms of Reelin activity. I also discuss possible strategies to enhance Reelin’s function. A complete understanding of Reelin function and its regulatory mechanisms in the adult central nervous system could help ameliorate neuropsychiatric and neurodegenerative disorders.